Innovative technologies for the recovery of phytochemicals from Stevia rebaudiana Bertoni leaves: A review. (1st December 2018) - Bursać Kovačević, Danijela; Maras, Marta; Barba, Francisco J.; Granato, Daniel; Roohinejad, Shahin; Mallikarjunan, Kumar; Montesano, Domenico; Lorenzo, Jose M.; Putnik, Predrag
Graphical abstract: Highlights: Recovery of bioactive compounds and steviol glycosides from Stevia is discussed. Innovative extraction techniques of phytochemicals from Stevia are explained. MAE, UAE, HPAE, PLE, SFE, PEF, HVED, cold plasma, and RSLDE. Abstract: Stevia rebaudiana Bertoni has gained increased industrial and scientific interests in the last 20 years, representing a suitable nutritional alternative to sucrose and artificial sweeteners. Moreover, this plant contains polyphenols, chlorophylls, and carotenoids that may be extracted for production of nutraceuticals and functional foods. Because of nutritional and technological advantages over sucrose, innovative approaches for the extraction of highly valued compounds from Stevia leaves have been developed and optimized. In contrast to conventional alternatives, innovative extraction methods allow higher yields in a shorter time, less usage of organic solvents, and reduced energy consumption. In this paper, the use of innovative extraction techniques: MAE, UAE, HPAE, PLE, SFE, PEF, HVED, cold plasma, and RSLDE for the recovery of non-nutrients with putative health benefits from Stevia leaves is discussed.